Programmatic implementation of depression screening and remote mental health support sessions for persons recently diagnosed with TB in Lima, Peru during the COVID-19 pandemic - Contreras, Carmen (2024)
Background: Few studies have explored a stepped care model for delivering mental health care to persons with tuberculosis (TB). Here, we evaluated depression screening and remote lowintensity mental health interventions for persons initiating TB treatment in Lima, Peru during the COVID-19 pandemic. Methods: We used the Patient Health Questionnaire 9 (PHQ-9) to screen participants for depressive symptoms (PHQ-9 ≥ 5). Participants with PHQ-9, 5–14 received remote Psychological First Aid (PFA) or Problem Management Plus (PM+). Participants were reevaluated 6 months after intervention completion. Wethen compared the change in median PHQ-9 scores before and after intervention completion. Those with PHQ-9 ≥ 15 were referred to higherlevel care. Findings: We found that 62 (45.9%) of the 135 participants had PHQ-9 ≥ 5 at baseline. Then, 54 individuals with PHQ-9, 5–9 received PFA, of which 44 (81.5%) were reevaluated. We observed significant reductions in median PHQ-9 scores from 6 to 2 (r = 0.98; p < 0.001). Four participants with PHQ-9, 10–14 received PM+ but were unable to be reevaluated. Four participants with PHQ-9 ≥ 15 were referred to higher-level care. Conclusions: Depressive symptoms were common among persons recently diagnosed with TB. We observed improvements in depressive symptoms 6 months later for most participants who received remote sessions of PFA.